MicroRNAs as mediators of drug resistance mechanisms. (October 2020) - Lampis, Andrea; Hahne, Jens C; Hedayat, Somaieh; Valeri, Nicola
Abstract : MicroRNAs are small RNA transcripts involved in fine-tuning of several cellular mechanisms and pathways crucial for maintaining cells' homeostasis like apoptosis, differentiation, inflammation and cell-cycle regulation. They act by regulation of gene expression at post-transcriptional level through fine-tuning of target proteins expression. Expression of microRNAs is cell-type specific and since their discovery they have been proven to be deregulated in various disorders including cancer. Several lines of evidence are emerging that link microRNAs to drug resistance mechanisms in tumours given their important role in modulating oncogenic and tumour suppressive mechanisms. This review will focus on latest knowledge of the roles and mechanisms of microRNAs as mediators to drug resistance and the implications for future therapies.